An Analysis of Teacher Strategies in Teaching Reading Comprehension through Online Learning to the Second Semester English Department Students of University of Islam Malang - Mochammad Anwar Haris (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
This study aimed to provide broader insight about teaching reading strategies which was implemented by a lecturer in online learning. A qualitative research design was used in this research. The researcher chose one of the senior reading lecturers of University of Islam Malang as the subject of the research. To collect the data, the researcher used some instruments such as observation, interview, questionnaire and documents. The finding of the study was indicated that the observed lecturer compiled teaching strategy since the lecturer made the lesson plan. The researcher found that the lecturer applied reciprocal strategy and QARs. The observed lecturer also implemented various activities. Besides, the students also gave positive perception regarding with the teaching strategies which were implemented by the lecturer. It was demanded further exploration and investigation about teaching reading strategy deeply in future research regarding all those findings.